High Activities of Nickel (Ii) Complexes Containing Phosphorus-Nitrogen Ligands in Hydrogen Transfer Reaction of Imines Using Formic Acid as a Renewable Hydrogen Source - Moya-Duran, S; Moya-Duran, S; Negrete-Vergara, C; Negrete-Vergara, C (Elsevier B.V., 2023)
The catalytic reduction of imines to obtain secondary amines is an important route in the synthesis of molecules of biological or pharmaceutical interest. A series of new nickel (II) complexes bearing phosphorous-nitrogen (P,N) or phosphorous-nitrogen-phosphorous (P,N,P) ligands were characterized and studied as catalysts in hydrogen transfer reaction of imines, using formic acid as a hydrogen source, while avoiding the use of molecular hydrogen (H2). The complexes, of general formula NiCl2(L), [Ni(L)2](CF3SO3)2 (in which L is a P,N ligand) and [NiCl(L)]Cl (in the case of a tridentate PNP ligand), were active catalysts in the imine hydrogen, with turnover frequencies (TOF) up to 373 h−1 with NiCl2L1 complex (L1 = 2-(diphenylphosphinoamino) pyridine) and N-benzylideneaniline as substrate, while a [Ni(L)2](CF3SO3)2 complex bearing the same P,N ligand achieved a slightly lower activity (TOF = 320 h−1). Catalyst recyclability was also studied, achieving near full conversion after four cycles, with a total substrate/catalyst ratio of 1000:1. © 2023